Advances in Smart Materials and Applications - Kuan, Yew Cheong; Kean, Aw; Karimov, Khasan S.; Feng, Zhao; Mohammad, Mahroof Tahir; Rupert, Schreiner (Hindawi Publishing Corporation, 2014)
This is one of a series of special issues published in Advances in Materials Science and Engineering, focusing on the latest advances of smart materials and their applications. Evolution of engineering materials is strongly depending on the growing transformation of complexity in engineering products. New materials being designed are required to provide specific properties and demonstrate certain functional characteristics by manipulating their dimension, chemistry, and structure through various advanced technologies.Therefore, “smartness” of a material has become the topic of interest. Properties of smart materials may change accordingly to the applied external stimuli. Under the direction of the editorial team, we showcase advances of organic and inorganic based smart materials and their applications in areas of specific interest such as energy, environment, and health. A total of 9 articles are published in this special issue. Six articles are focused on production, synthesis, and optimization of smart materials; and the remaining are dedicated to application of smart materials.